Geosynthetic as Sustainable Materials for Earthquake resistant of Masonry Structures. Issue 1 (November 2020) - Ali Khan, Hasim; Behera, Biplab; Prasad Nanda, Radhikesh
Abstract: When exposed to simultaneous in-plane and out-of-plane behaviour generated by earthquakes or high wind pressure, unreinforced masonry (URM) walls are vulnerable to failure. The paper presents the performance of brick masonry panels using non-woven geotextile in-plane shear and out-of-plane bending experimentally tested. The panels were reinforced with a diagonal geometric pattern on both sides. From the laboratory assessment, it was determined that geosynthetic enhancement significantly improved the capacity of load carrying, displacement capacity, bending moment, stiffness, diagonal shear, in-plane shear, and flexural strength with higher performance for both cases in the case of the cross pattern. In contrast to the un-strengthened panel, experimental findings have demonstrated a less fragile behaviour. Geosynthetics can therefore be preferably suited for strengthening the brick masonry panel in order to defend brick constructions in seismic populated places.